Why and for what competing if cooperating is the human essence? - Van de Velde, Herman (2012)
The international relation among the countries, characterized for being unfair and authoritarian, force us to act. The question is: How to act in a word ruled by a “meritocracy” where the success is defined by profit and money and not for solidarity and cooperation? We are led to believe that our human “essence” is related to compete among ourselves, even though the neo-liberal mentality leads us to the failure. While in such countries where an alternative system is constructed, the socioeconomic inequality decreases, thanks to a genuine cooperation among the countries. Also, in these societies (with less socioeconomic inequality) it is expressed a higher level of happiness with less health, education problems, or any other nature. The education based on competencies (focused on content) promotes the urge to compete, while an education based on cooperative attitudes (focused on methodology) facilitates and stimulates commitment as well as both personal and  ollective enjoyment, based on an inclusive, integral and integrating view and practice. Let us make our education a space for critical thinking, solidarity, social togetherness and cooperative endeavor. This has consequences at both macro and micro levels.